Corrosion Behavior of Various Surface Treatments TI-6Al-4V Alloy- A Review - Yusuf, Yusliza; Omar, Nooririnah; Azhari, Muhamad Azwar; Md Johari, Md Ashadi (Trans Tech Publications, 2013)
A Ti-6Al-4V alloy has been widely used as suitable materials for several of application such as aerospace, marine and biomedical application. Although this alloy is excellent in its properties and good corrosion resistance, the applications are limited because of their poor tribological property referring to the wear resistance property due to their low surface hardness. Therefore, it is inevitable to improve the wear properties of Ti-6Al-4V without detrimental the initial corrosion resistance properties even increasing it for better result. Over the years, various methods of surface treatments for Ti-6Al-4V have been studied and most frequently used are laser treatment, plasma nitriding process, PVD coating and also duplex coating. For each of the surface treatment discussed, several type of corrosion behavior have been studied with the conclusion is comparable to each other. In general, throughout these techniques, the wear resistance property of Ti-6Al-4V was improved and simultaneously improving the corrosion resistance property.